INSC Is Down-Regulated in Colon Cancer and Correlated to Immune Infiltration - Yu, Tao; Li, Dan; Zeng, Zhi; Xu, Xu; Zhang, Haiming; Wu, Jie; Song, Wei; Zhu, Hua (Frontiers in Genetics, 2022)
Background: Previous studies have verified that Inscuteable Spindle Orientation Adaptor Protein (INSC) could regulate cell proliferation and differentiation in the developing nervous system. It also plays an important role in spindle orientation during mitosis and asymmetric division of fibroblasts and participating in the process of stratification of the squamous epithelium. The role and potential mechanism of INSC in the development of Colonic adenocarcinoma (COAD) haven’t been fully understood. Aim: To explore the prognostic value of INSC in COAD and the correlation of its expression with immune infiltration. Methods: The Cancer Genome Atlas (TCGA), GTEx, GEPIA and Gene Expression Omnibus (GEO) database was used to analyze the expression of INSC in COAD. INSC protein expression level was analyzed with the HPA (proteinatlas.org) database. The diagnostic and prognostic value of INSC in COAD patients was analyzed using Receiver operating characteristic (ROC) and Kaplan- Meier (KM) survival curves. In order to understand whether INSC is an independent prognostic factor, we used univariable and multivariate Cox analyses to analyze INSC expression and several clinical characteristics with survival, we use STRING analysis to find INSC-related proteins, and related biological events analyzed by GO and KEGG analysis. At last, GEPIA and TIMER were employed to explore the relationship between INSC and immune infiltrates and its marker gene set. Results: INSC was lower expressed in COAD tissues than in normal colon tissues, which was correlated with tumor stage. Patients with lower expression of INSC had shorter overall survival (OS). Moreover, univariable cox analysis demonstrated that high expression of INSC was an independent prognostic factor for COAD. ROC analysis showed INSC was an accurate marker for identifying tumor from normal colon tissue and the AUC of the curve was 0.923. Significant GO term analysis by GSEA showed that genes correlated with INSC were found to be enriched in the several immune-related pathways. Specifically, INSC expression showed significant negative correlations with infiltration levels of B cell, CD4+ T cells, Macrophages, DCs and their marker sets in COAD. Conclusion: INSC was provided with prognostic value in COAD, and its mechanism may be related to immune invasion.